In living color? Understanding the importance of color complexity in listing images for accommodation sharing. (June 2022) - Barnes, Stuart J.
Abstract: The impact of color psychology on behavior has been clearly demonstrated for tangible products and advertising. However, the use of colors in combination has had little attention and has not been examined in the service context. This paper tests the small palette principal and the visual coherence perspective in an accommodation sharing setting. The studies are based on machine learning using large-scale data sets of US accommodation, with n = 1053 final images in study 1 and n = 1654 in study 2. Overall, the paper finds support for the small palette principal across the two studies. Study two tested the visual coherence perspective and found that significantly lower average distances between colors in perceptual space were found for listing images of properties with higher patronage. The implications are that in order to increase patronage, accommodation hosts should pay attention to the nature of color features of the listing images used for their properties.